Studi Komparasi Tipologi Pemikiran Islam: Liberal, Fundamentalis, dan Moderat - Abul Mafaakhir; Muhammad Hufron (Muaddib: Jurnal Pendidikan Agama Islam, 2023)
This study aims to understand the differences and similarities between the three dominant typologies of Islamic thought in the contemporary context, namely liberal, fundamentalist and moderate thought. Through a comparative analytical approach, this research explores the roots of thought, religious views, as well as the social and political implications of these three schools. Liberal Islamic thought tends to emphasize an open interpretation of Islamic teachings, emphasizing human rights, pluralism, and the separation of religion from politics. In contrast, fundamentalist thought adopts a more literal approach to religious texts, rejects the influence of secular culture, and advocates for the strict application of Islamic law in all aspects of life. Meanwhile, moderate Islamic thought tries to find a balance between Islamic traditions and the modern context, recognizing the values of diversity, tolerance and interreligious dialogue. Moderates try to absorb the essence of the Islamic message while adapting it to current developments, without ignoring the basic values of religion. This research uses a descriptive-analytic methodology by analyzing literature, speeches by religious figures, as well as official statements from related religious organizations. It is hoped that the findings from this study will provide a deeper understanding of the differences and similarities between the three typologies of Islamic thought, as well as their impact on social and political dynamics in contemporary society. The implications of this research can be used as a basis for supporting dialogue between religious communities, strengthening tolerance, and designing more inclusive policies at various levels of society.